Welfare reform in European countries: A micro-simulation analysis - Herwig Immervoll; Henrik Jacobsen Kleven; Claus Thustrup; Emmanuel Saez (University of Essex, Institute for Social and Economic Research (ISER), 2004)
This paper estimates the welfare and distributional impact of two types of welfare reform in 14 member countries of the European Union. The reforms are revenue neutral and ?nanced by an overall and uniform increase in marginal tax rates on earnings. The ?rst reform distributes the additional tax revenue uniformly to everybody (traditional welfare) while the second reform distributes tax proceeds uniformly to workers only (in-work bene?t). We build a simple model of labor supply encompassing responses to taxes and transfers along both the intensive and extensive margin. We then use EUROMOD to describe current welfare and tax systems in all European Union countries (except Sweden) and use calibrated labor supply elasticities along the intensive and extensive margins to analyze the e?ects of the two welfare reforms. We quantify the equity-e?ciency trade-o? for a range of elasticity parameters. In most countries, because of the large existing welfare programs with high phase-out rates, the uniform redistribution policy is, in general, undesirable unless the redistributive tastes of the government are extreme. The in-work bene?t reform, on the other hand, is desirable in a very wide set of cases. We discuss the practical policy implications for European welfare policy.
Keywords: 330; Sozialreform; Steuerreform; Arbeitsangebot; Simulation; EU-Staaten